A Novel Electric Power Generation Mechanism from Waste Heat without Temperature Gradient. Issue 60 (2nd May 2016) - Yamasoto, Keita; Osakabe, Yuki; Adachi, Sota; Munetoh, Shinji; Furukimi, Osamu
ABSTRACT: Seebeck effect is widely used for the energy harvesting from wasted heat. In the Seebeck effect, the electric power can be generated by the temperature difference between both ends of the thermoelectric materials. However, low conversion efficiency is caused by heat flux from hot side to cold side of sample. In this paper, we have proposed a new thermal power generation mechanism with no temperature difference. We investigated the band structure of Ba8 Aux Si46-x clathrate single crystal synthesized by Czochralski method. The single crystal has a gradient of the gold contents along the growth direction. According to the results of Seebeck coefficient, the electrical properties of the Ba8 Aux Si46-x clathrate dramatically changed depending on the gold contents. In the case of gold content of lower than 5.33, the Ba8 Aux Si46-x clathrate showed a n-type semiconductor. In the case of gold content of higher than 5.33, the Ba8 Aux Si46-x clathrate showed a p- type semiconductor. The band gap of the n- type and p- type Ba8 Aux Si46-x clathrate were wider than the intrinsic semiconductor. We can successfully synthesize a n-p junction single crystal, which obtaining energy band curve generated from the difference of Fermi level between p- and n- type semiconductors. The single crystal was heated under the uniform temperature and able to obtain generated electric voltage of around 0.6 mV at 400°C. These results suggested that the obtained electric voltage can be generated from the separation of hole-electron pair excited by heating at the intrinsic part with a narrow band gap along to the energy band curve formed by p-n junction.